دور نظام معلومات الإنتاج في مراقبة الإنتاج - دراسة ميدانية بمؤسسة صناعة الكوابل فرع جنرال كابل بسكرة- - أ.دالي علي, لمياء (Recherches économiques et managériales, 2014)
الملخص : نظام معلومات الإنتاج هو نظام فرعي من نظم المعلومات الإدارية، وهو يخدم وظيفة الإنتاج فيما يتعلق بتخطيط وجدولة الإنتاج ومراقبته، بما يضمن إنتاج وتوفير المنتجات للزبائن بالكميات المطلوبة والجودة المناسبة، وفي الوقت المناسب. يهدف هذا البحث إلى التعرف على أهمية نظام معلومات الإنتاج داخل المؤسسة الصناعية، وتوضيح كيفية مساهمته في مراقبة الإنتاج، من خلال المعلومات المقدمة عبر تقارير النشاط، وقد تم التوصل في هذا البحث إلى أن نظام معلومات الإنتاج بمؤسسة صناعة الكوابل - فرع جنرال كابل بسكرة - ، لا يساهم بشكل فعال في مراقبة الإنتاج، بسبب عدم تقديم معلومات ذات جودة (مثلا: خاصية الدقة، الموثوقية وخاصية التحيين) - وبالتالي فالرقابة لا تكون فعالة، وهذا ما يترجم في تكرار الانحرافات، وعدم اتخاذ الاجراءات التصحيحية الملائمة، ومنه فإن نجاح وظيفة مراقبة الإنتاج ترتبط بفعالية المعلومات المقدمة من طرف نظام معلومات الإنتاج. الكلمات المفتاحية: تقارير النشاط ، نظام معلومات الإنتاج، مراقبة الإنتاج.   Abstract : Production Information System is a subsystem of the MIS, which serves the function of production with respect to the planning, scheduling and monitoring of production, to ensure the production and supply of products to customers in the quantities required with appropriate quality and in the appropriate time. This research aims to identify the importance of production information system within an industrial enterprise and to clarify its contribution in the production control through information provided by activity reports. The conclusion of this article is the production information system in ENICAB-GENERAL CABLE Biskra does not effectively contribute to the production control because of the failure to provide quality information, and therefore, control is not effective, this translates the repeated gaps and the failure to take an appropriate corrective actions, because the success of the production function depends on the information provided by the production information system. Key words : activity reports, production information system, production control.